My first 100 words in French and English = [Mes premiers 100 mots en français et anglais] - Faulkner, Keith; Johnson, Paul (New York : Little Simon, 1998)
Provides illustrations of common everyday objects with the English word underneath. By pulling a pull-tab, the child can see the French version of each word.
2.5
K-3
Text in English and French.
Parallel title from back cover.
"A pull-the-tab language book"--Cover.
"Originally published in the United Kingdom by World International Pub. Ltd. as My first 100 French words"--P. before the t.p.
Keywords: Picture dictionaries, French -- Juvenile literature; Picture dictionaries, English -- Juvenile literature; Toy and movable books -- Specimens; Picture dictionaries; Toy and movable books; French language materials -- Bilingual; Picture dictionaries; Toy and movable books; Bilingual books -- English-French.